Influence of adding edible termite flour to Ogi powder: its chemical and phytochemical composition - Awoyale, W.; Fadeni, F.R.; Maziya-Dixon, B. (Frontiers Media, 2024)
Ogi, a traditional staple food made from submerged fermented cereal grains, is high in carbohydrates and low in protein. It is essential to conduct this research because termite flour (TF) addition may affect other quality aspects in addition to increasing protein content. Using 100 g of Ogi powder as a control sample, the chemical and phytochemical content of Ogi developed from blends of Ogi powder (OP) (50–100 g) with termite flour (TF) (10–50 g) was assessed using standard methods. The average proximate composition of the supplemented Ogi powder was 9.89% moisture, 3.87% fat, 2.59% crude fiber, 2.42% ash, 15.82% protein, and 65.41% total carbohydrates. Zinc is 3.19 mg/100 g while iron is 2.03 mg/100 g on average. Phytate (0.12 mg/100 g), oxalate (0.06 mg/100 g), saponin (0.73 mg/100 g), and tannin (0.02 mg/100 g) are phytochemical constituents. Though, supplemented Ogi powder of higher protein, ash, and iron contents than those of the control sample could be achieved by blending 50.0 g of OP with 50.0 g TF, 75.0 g of OP with 58.3 g TF, and 39.6 g OP with 30 g TF. However, blending 52.31% Ogi powder and 43.58% termite flour could produce a supplemented Ogi powder with nutritional and phytochemical constituents than those of the control sample. While the product could help lower the rate of protein-energy malnutrition, the supplemented Ogi powder’s amino acid, and carotenoid profiles need to be assessed.